An Investigation of the Role of Media Propaganda in Shaping Public Opinion in Modern America Case Study: Perception of the LGBTQ Community - Benghechoua, Abdelbaki; Benhacine ,Ayyoub; Mihoubi, Ahmed (Faculty of Letters and Foreign Languages Department of English, 2024)
The study aims to examine how the media played a crucial role in potentially altering public opinion to accept the LGTBQ community. This study explores the media's approaches to the LGBTQ issue in American society using Chomsky's propaganda model. The research analyzes media strategies and content that have influenced public perception through a methodological application of Chomsky's framework. The results indicate that the propaganda model remains relevant and effective in today's world. The results indicate that media campaigns and strategic narrative construction have significantly shifted public opinion towards an increased acceptance of the LGBTQ community. This shift is a further demonstration of the level of power that the media wields in influencing social attitudes and beliefs